Detection and Characterization of Conjugative Degradative Plasmids in Xenobiotic-Degrading Sphingomonas Strains - Basta, Tamara (American Society for Microbiology, 2004)
A systematic survey for the presence of plasmids in 17 different xenobiotic-degrading Sphingomonas strains was performed. In almost all analyzed strains, two to five plasmids with sizes of about 50 to 500 kb were detected by using pulsed-field gel electrophoresis. A comparison of plasmid preparations untreated or treated with S1 nuclease suggested that, in general, Sphingomonas plasmids are circular. Hybridization experiments with labeled gene probes suggested that large plasmids are involved in the degradation of dibenzo-p-dioxin, dibenzofuran, and naphthalenesulfonates in S. wittichii RW1, Sphingomonas sp. HH69, and S. xenophaga BN6, respectively. The plasmids which are responsible for the degradation of naphthalene, biphenyl, and toluene by S. aromaticivorans F199 (pNL1) and of naphthalenesulfonates by S. xenophaga BN6 (pBN6) were site-specifically labeled with a kanamycin resistance cassette. The conjugative transfer of these labeled plasmids was attempted with various bacterial strains as putative recipient strains. Thus, a conjugative transfer of plasmid pBN6 from S. xenophaga BN6 to a cured mutant of strain BN6 and to Sphingomonas sp. SS3 was observed. The conjugation experiments with plasmid pNL1 suggested a broader host range of this plasmid, because it was transferred without any obvious structural changes to S. yanoikuyae B1, Sphingomonas sp. SS3, and S. herbicidovorans. In contrast, major plasmid rearrangements were observed in the transconjugants after the transfer of plasmid pNL1 to Sphingomonas sp. HH69 and of pBN6 to Sphingomonas sp. SS3. No indications for the transfer of a Sphingomonas plasmid to bacteria outside of the Sphingomonadaceae were obtained.